Design of free‐standing microstructured conducting polymer films for enhanced particle removal from non‐uniform surfaces. Issue 19 (31st May 2016) - Laster, Jennifer S.; Deom, Nicholas A.; Beaudoin, Stephen P.; Boudouris, Bryan W.
ABSTRACT: Efficient removal of particles from topologically‐complex surfaces is of significant import for a range of applications (e.g., explosive residue removal in security arenas). Here, we synthesize next‐generation polymeric particle removal swabs with tuned structural features to elucidate the influence of the polymer microstructure on the removal of trace particles from surfaces. Specifically, microstructured free‐standing films of the conducting polymer polypyrrole (PPy) were synthesized through template‐assisted electropolymerization techniques. The removal of polystyrene microspheres from representative aluminum surfaces of varying roughness was evaluated as a function of the PPy microstructure. PPy‐based microstructured swabs displayed increased particle trapping properties relative to non‐textured PPy‐based swabs and current commercial swabs. This increased effectiveness occurred from the more intimate particle‐swab contact, leading to increased van der Waals interactions for the microstructured swabs. Therefore, this effort provides critical design rules for the production of microstructured conducting polymer materials for their application toward advanced particle removal technologies. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 1968–1974 Abstract : The removal of particles from surfaces is important for a variety of applications. Here, free‐standing microstructured films of the conducting polymer polypyrrole are developed for the specific application of enhanced contact sampling for the detection of trace explosives. The influence of the polymer microstructure on the removal of model particles from a representative aluminum substrate of varying roughness is studied.